Anterior Versus Posterior Approaches for Odontoid Fracture Stabilization in Patients Older Than 65 Years: 30-day Morbidity and Mortality in a National Database. Issue 8 (October 2017) - Patterson, Joseph T.; Theologis, Alexander A.; Sing, David; Tay, Bobby
Abstract : Study Design: Retrospective cohort analysis. Objective: To compare 30-day perioperative clinical outcomes of surgical odontoid stabilization by an anterior or posterior operative approach in elderly patients. Summary of Background Data: Surgical stabilization of odontoid fractures is superior to nonoperative management in geriatric patients. How elderly patients with odontoid fractures fare after anterior and posterior approaches, however, is not well defined. Materials and Methods: Retrospective review of the prospectively collected American College of Surgeons National Surgical Quality Improvement Program database (2005–2013). Elderly patients (≥65 y) with odontoid fractures who underwent odontoid stabilization through anterior or posterior approaches were identified by International Classification of Diseases 9th Revision/Common Procedure Terminology codes. Exclusion criteria included concomitant subaxial spine surgery, instrumentation noncontiguous with the atlantoaxial interval, and combined approaches. Baseline demographics and perioperative details were compared. Adverse events, mortality, reoperation, discharge, and readmission rates within 30 days of operation were compared using bivariate and multivariate generalized linear regressions. Results: One hundred forty-one patients (male—81; female—60; average age: 77.8±6.5 y; anterior approach—48; posterior approach—93) were analyzed. Patients scheduled to have a posterior approach had significantly more nonunions preoperatively and higher body mass indices. Operative times for posterior surgeries were significantly longer. Age, comorbidities, functional dependence, time to surgery, and length of hospital stay were similar between groups. There were no significant differences in the relative risk (RR) of the composite outcome of "any adverse event" after adjusting for differences in baseline characteristics. Patients who underwent an anterior approach were more likely to have an unplanned hospital readmission (RR=8.95; 95% confidence interval, 2.21–36.29; P =0.002) and have significantly more revision operations (RR=19.51; 95% confidence interval, 2.49–152.62; P =0.005) than patients who had a posterior operation. Conclusions: An anterior approach for odontoid fracture stabilization in patients ≥65 years old were associated with shorter operative times and greater RRs of unplanned readmissions and revision operations within 30 days of surgery relative to a posterior approach.